Non-small cell lung cancer with brain metastasis at presentation - Waqar, Saiama N. (Clin Lung Cancer, 2018)
BACKGROUND: Data on the prevalence of brain metastases at presentation in patients with non-small cell lung cancer (NSCLC) are limited. We queried the National Cancer Data Base (NCDB) to determine prevalence, clinical risk factors and outcomes of patients with NSCLC presenting with brain metastases. METHODS: Patients with NSCLC diagnosed between 2010 and 2012 were identified using the NCDB. The risk of brain metastases for individual variables was summarized by odds ratio (OR) and calculated using logistic regression analysis. Kaplan-Meier product limit method was used to calculate the median, 1 year, 2 year and 3 year overall survival (OS). RESULTS: Brain metastases were observed in 47,546 (10.4%) of the 457,481 patients with NSCLC overall. The prevalence of brain metastases was much higher (26%) in patients with stage IV disease at presentation. On multivariate analysis younger age, adenocarcinoma or large cell histology, tumor size > 3 cm, tumor grade ≥ II and node positive disease were associated with brain metastases. The prevalence of brain metastases ranged from as low as 0.57% in patients with only 1 risk factor to as high as 22% in patients with all 5 risk factors. The median, 1, 2 and 3-year OS for patients with brain metastases were 6 months 29.9%, 14.3% and 8.4% respectively, with the 3-year OS increasing to 36.2% in those with T1/2 and N0/1 undergoing surgery for the primary site. CONCLUSIONS: In patients with NSCLC, the risk of brain metastases at presentation may be calculated based on five clinical variables. Selected patients with brain metastases at presentation may achieve prolonged benefit.